Design Viability of Purse Seiners Operating in Bone Regency, South Sulawesi, Indonesia. (November 2019) - Farhum, S A; Zainuddin, M; Nelwan, A F P; Pangera, A A; Risa, R D
Abstract: The success of fishing operations is influenced by various factors that interact with each other, one of which is the fishing vessel. Purse seine fisheries make a substantial contribution to capture fisheries in much of eastern Indonesia, including the seas around Sulawesi. Purse seiners must conform to standard criteria to ensure the success of the catch. Therefore, this study aimed to explore the design viability of purse seiners operating from Bone Regency in South Sulawesi. This study evaluated four purse seiner vessels, measuring the main dimensions and curvature of the vessels to obtain vessel offset data. The data obtained were analysed using the Maxsurf V8.20i program to produce line drawings and calculate the three-dimensional (3D) hydrostatic and stability properties of the vessels. These were used to evaluate the design viability based on compatibility with standard criteria. The purse seiners operating in Bone Regency had a casco hull type design, with V-bottom bow sections and U-bottom stern sections. The vessels had a large cross-sectional area which allowed considerable space for the placement of the purse seine net and fishing catch. The ratio of the main dimensions and hydrostatic parameters of the sample vessels did not match the standard criteria for purse seine vessels. However, the results obtained for the static stability of the sampled vessels did meet standards that are in accordance with the criteria of the International Maritime Organization.